Grammar-translation method affects students’ reading comprehension and motivation - Rizky Kurniawan; M. Zaini Miftah; Zaitun Qamariah (International Journal of Research on English Teaching and Applied Linguistics, 2021)
In English teaching, teaching methods should be applied in the classroom for the successfulteaching activity. It is believed that the Grammar Translation Method (GTM) is effective forteaching reading comprehension and motivating students. This study investigated the effect ofGTM on students’ reading comprehension and their reading motivation at SMAN 4 PalangkaRaya, Kalimantan Tengah. The study applied a quasi-experimental research design. To beresearch participants, 30 students of the natural science class were as an experiment group,and 30 students of the social science class were as a control group taken with a cluster randomsampling. Data were collected using the reading test and questionnaire. The collected datawere then analyzed using one-way ANOVA with SPSS 20. The results showed that GTM hasa significant effect on students reading comprehension and reading motivation. It was foundthat the degree of freedom between group (DFb) = 2, the degree of freedom within group(DFw) = 87 (Ttable = 1.99), and Fvalue was 37.019. It showed that Fvalue was higher than Ttable (37.019 1.99). It means that Ha was accepted and Ho was rejected.